Improvements of magnetic suspension active vibration isolation for floating raft system - Yang, Beibei; Hu, Yefa; Vicario, Francesco; Zhang, Jinguang; Song, Chunsheng (International journal of applied electromagnetics and mechanics, 2017)
A floating raft system is a special double-layer isolation system aiming to reduce the level of noise and vibration and has been widely applied to many kinds of ships and submarines. It can isolate vibration of hosts and auxiliary machines and reduce the structural noise of ships and submarines effectively. It can also protect the equipments and instruments in ships and submarines from being damaged, and makes them to be operated properly when ships and submarines are subjected to external loads and sudden shocks. However, the floating raft system is generally a flexible structure and it is subject to multiple frequency disturbances. The design of control systems to enhance its isolation performance is an active area of research. This paper presents improvements achieved by using a dynamic step FXLMS controller whose main benefit is to balance convergence speed and steady-state error by making the convergence coefficient vary with time. The mathematical model of the dynamic system to be used in the controller is obtained by the observer/Kalman filter identification (OKID) method. The performance of the new solution (dynamic step size FXLMS with OKID model) is compared with previous work based on a fuzzy controller and a dynamic model identified via the prediction error method. Both simulated and experimental results confirm the validity and the benefits of the approach.